Viral suppression and adherence in adolescents living with HIV in rural Tanzania. - Ezekiel Luoga; James Okuma; Lilian Moshi; George Sigalla; Dorcas Mnzava; Daniel H Paris; Tracy R Glass; Fiona Vanobberghen; Maja Weisser; Getrud Joseph Mollel; KIULARCO working group (PLoS ONE)
Background Adolescents living with HIV (ALHIV) in sub-Saharan Africa are affected by poor treatment outcomes, likely a consequence of poor adherence. Objectives To assess viral suppression rates and evaluate factors associated with achieving viral suppression and maintaining treatment adherence among ALHIV in rural Tanzania. Methods Cross-sectional analysis of data from the Kilombero and Ulanga Antiretroviral Cohort in Ifakara, Tanzania, including adolescents aged 10-19 years on antiretroviral treatment (ART) ≥6 months at the time point of their first viral load (VL) measurement after implementation of routine VL testing from August 2017 through December 2023. VL ≥1000 copies/ml was considered unsuppressed. We assessed agreement between adherence measures (self-report, pill box return, pill count and visual analogy scale) and viral suppression. Logistic regression was used to determine factors associated with viral suppression. Results Of 319 included adolescents, 159 (50%) were male, 143 (45%) aged 10-13 years, 213 (74%) had disclosed their HIV status, 72 (23%) lived ≥50 kilometers from the clinic, 161 (55%) had a WHO stage III/IV and 80 (33%) had CD4 cell counts <500 cells/mm3. Overall, 249 (78%) adolescents were virally suppressed. Factors associated with viral suppression were having a CD4 cell count ≥500 cells/mm3 (adjusted Odds Ratio (aOR) 3.48; 95% CI 1.49-8.13) versus those with a CD4 cell count <500 cells/mm3, being on a dolutegravir-based regimen (aOR 12.6; 95% CI 2.50-68.7) versus those on a NNRTI based regimen. Female gender was associated with lower odds of having viral suppression (aOR 0.41; 95%CI 0.18-0.93). There was a weak to moderate agreement between adherence measures and VL suppression. Conclusion Adolescents in this rural cohort remain far behind the UNAIDS 95% viral suppression target with only 78% being virally suppressed. The weak to moderate associations between adherence assessment and viral suppression. Adolescents' HIV care models need to be strengthened in order to achieve viral suppression goals in this population.